LEFT HEART DYSFUNCTION AND HEART VALVE DISEASE DO NOT INFLUENCE OUTCOMES AFTER LOWER LIMB REVASCULARIZATION - Correia, Ricardo (2021)
Introduction: Inadequate systemic perfusion as a consequence of heart disease may compromise inflow to lower limb revascularization procedures, decreasing short and mid-term patency. It may be theorized that patients suffering from heart valve disease or reduction of left ventricular ejection fraction (LVEF) have worse limb outcomes after lower limb revascularization. Method: This retrospective study included all first lower limb revascularization procedures performed in a tertiary hospital, between January 2017 and December 2018, in patients with diagnosed PAD and an available preoperative transthoracic echocardiogram (TTE). The group with moderate to severe heart disease in TTE (Group 1, defined as LVEF<40% or moderate to severe valvular heart disease) was compared against the group with no or mild heart disease in TTE (Group 2, defined as LVEF≥40% and no or mild valvular heart disease). Subgroup analysis was undertaken considering the presence and severity of the individual heart change on TTE. Primary endpoint was major amputation, and secondary endpoints were diagnosed restenosis/occlusion, vascular reintervention and overall survival. Results: The study included 268 lower limb revascularization procedures. Group 1 and 2 included 70 and 198 procedures, respectively. In both groups, the prevalence of CLTI was 89%. There were no significant differences in wound and infection grading (in WIfI), and anatomic disease staging (in GLASS), between Groups 1 and 2. In Group 1, 73% were endovascular procedures (65% in Group 2; p=0,34). Amputation rates in Group 1 and 2 were 9% and 13% at 1 month, 19% and 20% at 1 year and 19% and 22% at 2 years, respectively (p=0,758). Diagnosed restenosis/occlusion rates in Group 1 and 2 were 5% and 15% at 1 month, 18% and 26% at 1 year and 24% and 31% at 2 years, respectively (p=0,119). Reintervention rates in Group 1 and 2 were 13% and 18% at 1 month, 25% and 27% at 1 year and 30% and 32% at 2 years, respectively (p=0,614). After subgroup analysis according to the presence and severity of individual heart change, the difference remained non-significant for the above-mentioned outcomes. Overall survival in Group 1 and 2 was 92% and 96% at 1 month, 61% and 86% at 1 year and 52% and 80% at 2 years, respectively (p<0,001). LVEF<40% was associated with worse overall survival (p<0,001), as was moderate to severe valvular heart disease (p=0,004). Conclusion: Our study suggests that moderate to severe heart disease, detected in TTE, does not influence limb-related outcomes after revascularization procedures. However, patients with valvular heart disease or LVEF reduction have worse overall survival. We should not expect worse limb outcomes in patients with heart disease, but aggressive tertiary prevention should be provided to improve vital prognosis.